Phenomenological Study of Forgiveness in Adolescents with Dysfunction Family - Palionamo, Rafael James; Meliana, Meliana; Agustina, Fauziah Riyanti; Rahmatika, Aufilana; Saputri, Indriana Eka; Sampurno, Mukhsin Budi (Merpsy Journal, 2024)
This study aims to determine the forgiveness of adolescents who do not get emotional family support. The approach used in this study is a qualitative approach. Until this study were teenagers who live in Surakarta with a sample of four people. The results showed that three subjects had forgiven their parents’ behavior and one subject had not forgiven their parents.